MOTIVASI, LINGKUNGAN, DISIPLIN, SERTA SEMANGAT KERJA PENGARUHNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Indra Istanto, ; Jusuf Kasrori, (Pendidikan Ekonomi, 2009)
Workers productivity has close relationship with the competency of each worker, that is to improve work. Productivity of a company refers to the demand of needs by Maslow.  This research is aimed to know whether motivation, environment, discipline, and work spirit have an effect on workers productivity at production division of  PG. Gempolkrep Mojokerto. The population was the workers of production division at PG. Gempolkrep Mojokerto which consisted of 140 person.  103 person were chosen as  respondents by using proportional random sampling technique. Then,  the data obtained with questionnaire were analyzed with multiple linier regression analysis aided with SPSS programers 11.5 for windows.